1996
DOI: 10.1046/j.1468-2982.1996.1605328.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-Marketing Cohort Study Comparing the Safety and Efficacy of Flunarizine and Propranolol in the Prophylaxis of Migraine

Abstract: A comparative post-marketing surveillance study of the safety and efficacy of flunarizine and propranolol in the treatment of migraine was carried out. General practitioners in Belgium and the Netherlands each recruited patients for whom they would prescribe one of the study medications in the normal course of their treatment and recorded all medical events on follow-up forms for up to 8 months. A total of 1601 migraine patients were enrolled; 838 in the flunarizine cohort and 763 in the propranolol cohort. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…compared the efficacy of flunarizine and propranolol treatments in children with migraine and reported a similar level of decrease in the frequency of migraine attacks, while propranolol also reduced the severity of attacks. The efficacy of flunarizine and propranolol were assessed in a Belgian study conducted with adults with migraines and this concluded that propranolol was more efficient than flunarizine in reducing the severity of the migraine attacks . Luo et al.…”
Section: Discussionmentioning
confidence: 99%
“…compared the efficacy of flunarizine and propranolol treatments in children with migraine and reported a similar level of decrease in the frequency of migraine attacks, while propranolol also reduced the severity of attacks. The efficacy of flunarizine and propranolol were assessed in a Belgian study conducted with adults with migraines and this concluded that propranolol was more efficient than flunarizine in reducing the severity of the migraine attacks . Luo et al.…”
Section: Discussionmentioning
confidence: 99%
“…26 Studies were conducted in Germany, [21][22][23] Austria, 24 Belgium, 26 the Netherlands, 27 and Brazil. 25 Dosages varied by individual patient but were within the range of approved FDA-labeled dose for migraine prophylaxis, where applicable.…”
Section: Observational Studies: Persistencementioning
confidence: 99%
“…Migraine is a chronic disease often requiring long‐term management. Clinical trials assessing the effectiveness of extended drug treatment for migraine prevention (≥1 year) are few in number 6,19,20 . Three large pivotal clinical trials have demonstrated the ability of topiramate 100 and 200 mg/d to significantly reduce mean monthly migraine frequency during a 6‐month period 9‐11 .…”
Section: Commentsmentioning
confidence: 99%
“…Clinical trials assessing the effectiveness of extended drug treatment for migraine prevention (≥1 year) are few in number. 6,19,20 Three large pivotal clinical trials have demonstrated the ability of topiramate 100 and 200 mg/d to significantly reduce mean monthly migraine frequency during a 6-month period. 9−11 For the open-label extension phase of the 2 North American pivotal trials, 9,10 open-label topiramate was titrated to a clinically effective dose based upon physician judgment of response, which allowed patients to receive topiramate for up to 14 months.…”
Section: Commentsmentioning
confidence: 99%